TINJAUAN YURIDIS KLAUSULA BAKU PADA TIKET SPEEDBOAT SINERGI CIPTA MANDIRI RUTE KOTA PONTIANAK-KAB KAYONG UTARA - NIM. A1011211136, CHANIA ELGA NINDYA (Jurnal Fatwa Hukum, 2025)
Abstract  This study aims to analyze the standard clauses that occur as a result of the transportation agreement between the carrier and passengers of the Sinergi Cipta Mandiri speedboat on the Pontianak-Kayong Utara route. The formulation of the problem in this study is "What is the legal awareness of passengers to the terms and conditions that have been made by the Sinergi Cipta Mandiri Speedboat transportation service?" and "What efforts can be made by the transportation service in increasing the legal awareness of passengers to understand and respect the terms and conditions that have been set by the transportation service on the Sinergi Cipta Mandiri Speedboat ticket?". The approach method used is empirical. By using primary data and secondary data. Primary data was obtained directly through the results of interviews, observations and documentation from the main sources, namely the Sinergi Cipta Mandiri Speedboat Staff, and questionnaires distributed to passengers. Secondary data is data obtained through literature studies in the form of written materials such as legal and scientific books, legal journals and laws and regulations related to the issues discussed in the research. The result of the analysis of this study is that the carrier service has indeed limited itself to full responsibility for the passenger's luggage. This has been stated in point 4 on the terms and conditions on the back of the Speedboat ticket. However, regarding the terms and conditions that have been set by the transportation service, it turns out that there are still some passengers who do not know about the terms and conditions that have been set by the transportation service on the back of the travel ticket. In addition, transportation services have not been optimal in making efforts so that passengers can read, understand and understand these terms and conditions. Transportation services are expected to make several efforts such as notifying them again regarding these terms and conditions or pasting billboards at ticket sales places.  Keywords : Agreement, Water Transportation, Speedboat Synergy Cipta Mandiri  Abstrak  Penelitian ini bertujuan untuk mengalisa klausula baku yang terjadi akibat perjanjian pengangkutan antara pengangkut dan penumpang speedboat Sinergi Cipta Mandiri rute Pontianak-Kayong Utara. Rumusan masalah dalam penelitian ini adalah "Bagaimana kesadaran hukum penumpang terhadap syarat dan ketentuan yang telah dibuat oleh jasa pengangkut Speedboat Sinergi Cipta Mandiri?" dan "Upaya yang dapat dilakukan jasa pengangkut dalam meningkatkan kesadaran hukum penumpang untuk memahami dan menghormati syarat dan ketentuan yang telah ditetapkan oleh jasa pengangkut pada tiket Speedboat Sinergi Cipta Mandiri?". Metode pendekatan yang digunakan adalah empiris. Dengan menggunakan data primer dan data sekunder. Data primer diperoleh secara langsung melalui hasil wawancara, observasi dan dokumentasi dari sumber utama yaitu Staff Speedboat Sinergi Cipta Mandiri, dan kuesioner yang dibagikan kepada penumpang. Data sekunder ialah data yang diperoleh melalui studi kepustakaan yang berupa bahan tertulis seperti buku-buku hukum dan ilmiah, jurnal hukum serta peraturan perundang undangan yang berhubungan dengan masalah yang dibahas didalam penelitian. Hasil analisis dari penelitian ini adalah bahwa Jasa pengangkut memang telah membatasi dirinya untuk bertanggung jawab penuh terhadap barang bawaan penumpang. Hal ini telah dicantumkan pada poin ke-4 pada syarat dan ketentuan yang terdapat pada belakang tiket Speedboat. Namun terkait syarat dan ketentuan yang telah ditetapkan oleh jasa pengangkut tersebut ternyata masih terdapat beberapa penumpang yang belum mengetahui terkait adanya syarat dan ketentuan yang telah ditetapkan oleh jasa pengangkut pada belakang tiket perjalanan. Selain itu jasa pengangkut belum optimal dalam melakukan upaya agar penumpang dapat membaca, memahami dan mengerti terkait syarat dan ketentuan tersebut. Jasa pengangkut diharpkan dapat melakukan beberapa upaya seperti memberitahukan kembali terkait syarat dan ketentuan tersebut atau menempelkan baliho pada tempat penjualan tiket.Kata Kunci : Perjanjian, Pengangkutan Perairan, Speedboat Sinergi Cipta Mandiri